Resources in the Implementation of e-Tilang Program at the Sidoarjo District Attorney - Esa Citra Anindya; Ahmad Riyadh U.B (Indonesian Journal of Public Policy Review, 2022)
The purpose of this study was to describe and analyze the implementation of the e-Tilang program at the Sidoarjo District Attorney's Office. The method used in this study is a qualitative descriptive method with data collection techniques in the form of interviews, observations, dan documenattion. The technique of deternnining infornnants used sampling purposive, and data analysis was carried out with data reduction, collection techniques,conclusion and data presentation. The results of this study indicate that there are several types of supporting and inhibiting factors, there are several dimensions related to this research, namely (1) Communication, communication between agencies is interconnected well starting from the Police, the District Attorney and from the BRI (2) Resources , in terms of resources that are quite adequate although there are still some shortcomings, among others, human resources that are still not very familiar with e-Tilang due to the lack of training period and also servers that do not meet the standards, (3) Economic, Social and Political Environment , in terms of the political environment, increasing the productivity of its performance to be more effective and efficient as well as service-oriented and reducing acts of Corruption, Collusion and Nepotism (KKN) on the part of the Police and the Prosecutor's Office. Meanwhile, other inhibiting factors needed are increased socialization to the community which should be carried out in order to facilitate the ticketing process in the future.